Documentation

Mathlib.Algebra.Order.Monoid.Unbundled.WithTop

Adjoining top/bottom elements to ordered monoids. #

instance WithTop.one {α : Type u} [One α] :
Equations
instance WithTop.zero {α : Type u} [Zero α] :
Equations
@[simp]
theorem WithTop.coe_one {α : Type u} [One α] :
1 = 1
@[simp]
theorem WithTop.coe_zero {α : Type u} [Zero α] :
0 = 0
@[simp]
theorem WithTop.coe_eq_one {α : Type u} [One α] {a : α} :
a = 1 a = 1
@[simp]
theorem WithTop.coe_eq_zero {α : Type u} [Zero α] {a : α} :
a = 0 a = 0
@[simp]
theorem WithTop.one_eq_coe {α : Type u} [One α] {a : α} :
1 = a a = 1
@[simp]
theorem WithTop.zero_eq_coe {α : Type u} [Zero α] {a : α} :
0 = a a = 0
@[simp]
theorem WithTop.top_ne_one {α : Type u} [One α] :
@[simp]
theorem WithTop.top_ne_zero {α : Type u} [Zero α] :
@[simp]
theorem WithTop.one_ne_top {α : Type u} [One α] :
@[simp]
theorem WithTop.zero_ne_top {α : Type u} [Zero α] :
@[simp]
theorem WithTop.untop_one {α : Type u} [One α] :
untop 1 = 1
@[simp]
theorem WithTop.untop_zero {α : Type u} [Zero α] :
untop 0 = 0
@[simp]
theorem WithTop.untopD_one {α : Type u} [One α] (d : α) :
untopD d 1 = 1
@[simp]
theorem WithTop.untopD_zero {α : Type u} [Zero α] (d : α) :
untopD d 0 = 0
@[deprecated WithTop.untopD_zero (since := "2025-02-06")]
theorem WithTop.untop_zero' {α : Type u} [Zero α] (d : α) :
untopD d 0 = 0

Alias of WithTop.untopD_zero.

@[deprecated WithTop.untopD_one (since := "2025-02-06")]
theorem WithTop.untop_one' {α : Type u} [One α] (d : α) :
untopD d 1 = 1

Alias of WithTop.untopD_one.

@[simp]
theorem WithTop.one_le_coe {α : Type u} [One α] [LE α] {a : α} :
1 a 1 a
@[simp]
theorem WithTop.coe_nonneg {α : Type u} [Zero α] [LE α] {a : α} :
0 a 0 a
@[simp]
theorem WithTop.coe_le_one {α : Type u} [One α] [LE α] {a : α} :
a 1 a 1
@[simp]
theorem WithTop.coe_le_zero {α : Type u} [Zero α] [LE α] {a : α} :
a 0 a 0
@[simp]
theorem WithTop.one_lt_coe {α : Type u} [One α] [LT α] {a : α} :
1 < a 1 < a
@[simp]
theorem WithTop.coe_pos {α : Type u} [Zero α] [LT α] {a : α} :
0 < a 0 < a
@[simp]
theorem WithTop.coe_lt_one {α : Type u} [One α] [LT α] {a : α} :
a < 1 a < 1
@[simp]
theorem WithTop.coe_lt_zero {α : Type u} [Zero α] [LT α] {a : α} :
a < 0 a < 0
@[simp]
theorem WithTop.map_one {α : Type u} [One α] {β : Type u_1} (f : αβ) :
map f 1 = (f 1)
@[simp]
theorem WithTop.map_zero {α : Type u} [Zero α] {β : Type u_1} (f : αβ) :
map f 0 = (f 0)
theorem WithTop.map_eq_one_iff {β : Type v} {α : Type u_1} {f : αβ} {v : WithTop α} [One β] :
map f v = 1 (x : α), v = x f x = 1
theorem WithTop.map_eq_zero_iff {β : Type v} {α : Type u_1} {f : αβ} {v : WithTop α} [Zero β] :
map f v = 0 (x : α), v = x f x = 0
theorem WithTop.one_eq_map_iff {β : Type v} {α : Type u_1} {f : αβ} {v : WithTop α} [One β] :
1 = map f v (x : α), v = x f x = 1
theorem WithTop.zero_eq_map_iff {β : Type v} {α : Type u_1} {f : αβ} {v : WithTop α} [Zero β] :
0 = map f v (x : α), v = x f x = 0
instance WithTop.zeroLEOneClass {α : Type u} [One α] [Zero α] [LE α] [ZeroLEOneClass α] :
instance WithTop.add {α : Type u} [Add α] :
Equations
@[simp]
theorem WithTop.coe_add {α : Type u} [Add α] (a b : α) :
↑(a + b) = a + b
@[simp]
theorem WithTop.top_add {α : Type u} [Add α] (x : WithTop α) :
@[simp]
theorem WithTop.add_top {α : Type u} [Add α] (x : WithTop α) :
@[simp]
theorem WithTop.add_eq_top {α : Type u} [Add α] {x y : WithTop α} :
x + y = x = y =
theorem WithTop.add_ne_top {α : Type u} [Add α] {x y : WithTop α} :
@[simp]
theorem WithTop.add_lt_top {α : Type u} [Add α] {x y : WithTop α} [LT α] :
x + y < x < y <
theorem WithTop.add_eq_coe {α : Type u} [Add α] {a b : WithTop α} {c : α} :
a + b = c (a' : α), (b' : α), a' = a b' = b a' + b' = c
theorem WithTop.add_coe_eq_top_iff {α : Type u} [Add α] {x : WithTop α} {b : α} :
x + b = x =
theorem WithTop.coe_add_eq_top_iff {α : Type u} [Add α] {y : WithTop α} {a : α} :
a + y = y =
theorem WithTop.add_right_inj {α : Type u} [Add α] {x y z : WithTop α} [IsRightCancelAdd α] (hz : z ) :
x + z = y + z x = y
theorem WithTop.add_right_cancel {α : Type u} [Add α] {x y z : WithTop α} [IsRightCancelAdd α] (hz : z ) (h : x + z = y + z) :
x = y
theorem WithTop.add_left_inj {α : Type u} [Add α] {x y z : WithTop α} [IsLeftCancelAdd α] (hx : x ) :
x + y = x + z y = z
theorem WithTop.add_left_cancel {α : Type u} [Add α] {x y z : WithTop α} [IsLeftCancelAdd α] (hx : x ) (h : x + y = x + z) :
y = z
@[deprecated WithTop.add_left_inj (since := "2025-02-19")]
theorem WithTop.add_left_cancel_iff {α : Type u} [Add α] {x y z : WithTop α} [IsLeftCancelAdd α] (hx : x ) :
x + y = x + z y = z

Alias of WithTop.add_left_inj.

@[deprecated WithTop.add_right_inj (since := "2025-02-19")]
theorem WithTop.add_right_cancel_iff {α : Type u} [Add α] {x y z : WithTop α} [IsRightCancelAdd α] (hz : z ) :
x + z = y + z x = y

Alias of WithTop.add_right_inj.

instance WithTop.addLeftMono {α : Type u} [Add α] [LE α] [AddLeftMono α] :
instance WithTop.addRightMono {α : Type u} [Add α] [LE α] [AddRightMono α] :
theorem WithTop.le_of_add_le_add_left {α : Type u} [Add α] {x y z : WithTop α} [LE α] [AddLeftReflectLE α] (hx : x ) :
x + y x + zy z
theorem WithTop.le_of_add_le_add_right {α : Type u} [Add α] {x y z : WithTop α} [LE α] [AddRightReflectLE α] (hz : z ) :
x + z y + zx y
theorem WithTop.add_lt_add_left {α : Type u} [Add α] {x y z : WithTop α} [LT α] [AddLeftStrictMono α] (hx : x ) :
y < zx + y < x + z
theorem WithTop.add_lt_add_right {α : Type u} [Add α] {x y z : WithTop α} [LT α] [AddRightStrictMono α] (hz : z ) :
x < yx + z < y + z
theorem WithTop.add_le_add_iff_left {α : Type u} [Add α] {x y z : WithTop α} [LE α] [AddLeftMono α] [AddLeftReflectLE α] (hx : x ) :
x + y x + z y z
theorem WithTop.add_le_add_iff_right {α : Type u} [Add α] {x y z : WithTop α} [LE α] [AddRightMono α] [AddRightReflectLE α] (hz : z ) :
x + z y + z x y
theorem WithTop.add_lt_add_iff_left {α : Type u} [Add α] {x y z : WithTop α} [LT α] [AddLeftStrictMono α] [AddLeftReflectLT α] (hx : x ) :
x + y < x + z y < z
theorem WithTop.add_lt_add_iff_right {α : Type u} [Add α] {x y z : WithTop α} [LT α] [AddRightStrictMono α] [AddRightReflectLT α] (hz : z ) :
x + z < y + z x < y
theorem WithTop.add_lt_add_of_le_of_lt {α : Type u} [Add α] {w x y z : WithTop α} [Preorder α] [AddLeftStrictMono α] [AddRightMono α] (hw : w ) (hwy : w y) (hxz : x < z) :
w + x < y + z
theorem WithTop.add_lt_add_of_lt_of_le {α : Type u} [Add α] {w x y z : WithTop α} [Preorder α] [AddLeftMono α] [AddRightStrictMono α] (hx : x ) (hwy : w < y) (hxz : x z) :
w + x < y + z
theorem WithTop.addLECancellable_of_ne_top {α : Type u} [Add α] {x : WithTop α} [Preorder α] [ContravariantClass α α (fun (x1 x2 : α) => x1 + x2) fun (x1 x2 : α) => x1 x2] (hx : x ) :
theorem WithTop.addLECancellable_of_lt_top {α : Type u} [Add α] {x : WithTop α} [Preorder α] [ContravariantClass α α (fun (x1 x2 : α) => x1 + x2) fun (x1 x2 : α) => x1 x2] (hx : x < ) :
theorem WithTop.addLECancellable_coe {α : Type u} [Add α] [Preorder α] [ContravariantClass α α (fun (x1 x2 : α) => x1 + x2) fun (x1 x2 : α) => x1 x2] (a : α) :
theorem WithTop.addLECancellable_iff_ne_top {α : Type u} [Add α] {x : WithTop α} [Nonempty α] [Preorder α] [ContravariantClass α α (fun (x1 x2 : α) => x1 + x2) fun (x1 x2 : α) => x1 x2] :
@[simp]
theorem WithTop.map_add {α : Type u} {β : Type v} [Add α] {F : Type u_1} [Add β] [FunLike F α β] [AddHomClass F α β] (f : F) (a b : WithTop α) :
map (⇑f) (a + b) = map (⇑f) a + map (⇑f) b
instance WithTop.addMonoid {α : Type u} [AddMonoid α] :
Equations
@[simp]
theorem WithTop.coe_nsmul {α : Type u} [AddMonoid α] (a : α) (n : ) :
↑(n a) = n a
def WithTop.addHom {α : Type u} [AddMonoid α] :

Coercion from α to WithTop α as an AddMonoidHom.

Equations
Instances For
    @[simp]
    theorem WithTop.coe_addHom {α : Type u} [AddMonoid α] :
    @[simp]
    theorem WithTop.coe_natCast {α : Type u} [AddMonoidWithOne α] (n : ) :
    n = n
    @[simp]
    theorem WithTop.top_ne_natCast {α : Type u} [AddMonoidWithOne α] (n : ) :
    n
    @[simp]
    theorem WithTop.natCast_ne_top {α : Type u} [AddMonoidWithOne α] (n : ) :
    n
    @[simp]
    theorem WithTop.natCast_lt_top {α : Type u} [AddMonoidWithOne α] [LT α] (n : ) :
    n <
    @[simp]
    theorem WithTop.coe_ofNat {α : Type u} [AddMonoidWithOne α] (n : ) [n.AtLeastTwo] :
    @[simp]
    theorem WithTop.coe_eq_ofNat {α : Type u} [AddMonoidWithOne α] (n : ) [n.AtLeastTwo] (m : α) :
    @[simp]
    theorem WithTop.ofNat_eq_coe {α : Type u} [AddMonoidWithOne α] (n : ) [n.AtLeastTwo] (m : α) :
    @[simp]
    theorem WithTop.map_ofNat {α : Type u} {β : Type v} [AddMonoidWithOne α] {f : αβ} (n : ) [n.AtLeastTwo] :
    map f (OfNat.ofNat n) = (f (OfNat.ofNat n))
    @[simp]
    theorem WithTop.map_natCast {α : Type u} {β : Type v} [AddMonoidWithOne α] {f : αβ} (n : ) :
    map f n = (f n)
    theorem WithTop.map_eq_ofNat_iff {α : Type u} {β : Type v} [AddMonoidWithOne α] {f : βα} {n : } [n.AtLeastTwo] {a : WithTop β} :
    map f a = OfNat.ofNat n (x : β), a = x f x = n
    theorem WithTop.ofNat_eq_map_iff {α : Type u} {β : Type v} [AddMonoidWithOne α] {f : βα} {n : } [n.AtLeastTwo] {a : WithTop β} :
    OfNat.ofNat n = map f a (x : β), a = x f x = n
    theorem WithTop.map_eq_natCast_iff {α : Type u} {β : Type v} [AddMonoidWithOne α] {f : βα} {n : } {a : WithTop β} :
    map f a = n (x : β), a = x f x = n
    theorem WithTop.natCast_eq_map_iff {α : Type u} {β : Type v} [AddMonoidWithOne α] {f : βα} {n : } {a : WithTop β} :
    n = map f a (x : β), a = x f x = n
    @[simp]
    theorem WithTop.one_lt_top {α : Type u} [One α] [LT α] :
    1 <
    @[simp]
    theorem WithTop.top_pos {α : Type u} [Zero α] [LT α] :
    0 <
    @[deprecated WithTop.top_pos (since := "2024-10-22")]
    theorem WithTop.zero_lt_top {α : Type u} [Zero α] [LT α] :
    0 <

    Alias of WithTop.top_pos.

    @[deprecated WithTop.coe_pos (since := "2024-10-22")]
    theorem WithTop.zero_lt_coe {α : Type u} [Zero α] [LT α] (a : α) :
    0 < a 0 < a
    def OneHom.withTopMap {M : Type u_1} {N : Type u_2} [One M] [One N] (f : OneHom M N) :

    A version of WithTop.map for OneHoms.

    Equations
    Instances For
      def ZeroHom.withTopMap {M : Type u_1} {N : Type u_2} [Zero M] [Zero N] (f : ZeroHom M N) :

      A version of WithTop.map for ZeroHoms

      Equations
      Instances For
        @[simp]
        theorem OneHom.withTopMap_apply {M : Type u_1} {N : Type u_2} [One M] [One N] (f : OneHom M N) :
        @[simp]
        theorem ZeroHom.withTopMap_apply {M : Type u_1} {N : Type u_2} [Zero M] [Zero N] (f : ZeroHom M N) :
        def AddHom.withTopMap {M : Type u_1} {N : Type u_2} [Add M] [Add N] (f : M →ₙ+ N) :

        A version of WithTop.map for AddHoms.

        Equations
        Instances For
          @[simp]
          theorem AddHom.withTopMap_apply {M : Type u_1} {N : Type u_2} [Add M] [Add N] (f : M →ₙ+ N) :
          def AddMonoidHom.withTopMap {M : Type u_1} {N : Type u_2} [AddZeroClass M] [AddZeroClass N] (f : M →+ N) :

          A version of WithTop.map for AddMonoidHoms.

          Equations
          Instances For
            @[simp]
            theorem AddMonoidHom.withTopMap_apply {M : Type u_1} {N : Type u_2} [AddZeroClass M] [AddZeroClass N] (f : M →+ N) :
            instance WithBot.one {α : Type u} [One α] :
            Equations
            instance WithBot.zero {α : Type u} [Zero α] :
            Equations
            @[simp]
            theorem WithBot.coe_one {α : Type u} [One α] :
            1 = 1
            @[simp]
            theorem WithBot.coe_zero {α : Type u} [Zero α] :
            0 = 0
            @[simp]
            theorem WithBot.coe_eq_one {α : Type u} [One α] {a : α} :
            a = 1 a = 1
            @[simp]
            theorem WithBot.coe_eq_zero {α : Type u} [Zero α] {a : α} :
            a = 0 a = 0
            @[simp]
            theorem WithBot.one_eq_coe {α : Type u} [One α] {a : α} :
            1 = a a = 1
            @[simp]
            theorem WithBot.zero_eq_coe {α : Type u} [Zero α] {a : α} :
            0 = a a = 0
            @[simp]
            theorem WithBot.bot_ne_one {α : Type u} [One α] :
            @[simp]
            theorem WithBot.bot_ne_zero {α : Type u} [Zero α] :
            @[simp]
            theorem WithBot.one_ne_bot {α : Type u} [One α] :
            @[simp]
            theorem WithBot.zero_ne_bot {α : Type u} [Zero α] :
            @[simp]
            theorem WithBot.unbot_one {α : Type u} [One α] :
            unbot 1 = 1
            @[simp]
            theorem WithBot.unbot_zero {α : Type u} [Zero α] :
            unbot 0 = 0
            @[simp]
            theorem WithBot.unbotD_one {α : Type u} [One α] (d : α) :
            unbotD d 1 = 1
            @[simp]
            theorem WithBot.unbotD_zero {α : Type u} [Zero α] (d : α) :
            unbotD d 0 = 0
            @[deprecated WithBot.unbotD_zero (since := "2025-02-06")]
            theorem WithBot.unbot_zero' {α : Type u} [Zero α] (d : α) :
            unbotD d 0 = 0

            Alias of WithBot.unbotD_zero.

            @[deprecated WithBot.unbotD_one (since := "2025-02-06")]
            theorem WithBot.unbot_one' {α : Type u} [One α] (d : α) :
            unbotD d 1 = 1

            Alias of WithBot.unbotD_one.

            @[simp]
            theorem WithBot.one_le_coe {α : Type u} [One α] {a : α} [LE α] :
            1 a 1 a
            @[simp]
            theorem WithBot.coe_nonneg {α : Type u} [Zero α] {a : α} [LE α] :
            0 a 0 a
            @[simp]
            theorem WithBot.coe_le_one {α : Type u} [One α] {a : α} [LE α] :
            a 1 a 1
            @[simp]
            theorem WithBot.coe_le_zero {α : Type u} [Zero α] {a : α} [LE α] :
            a 0 a 0
            @[simp]
            theorem WithBot.one_lt_coe {α : Type u} [One α] {a : α} [LT α] :
            1 < a 1 < a
            @[simp]
            theorem WithBot.coe_pos {α : Type u} [Zero α] {a : α} [LT α] :
            0 < a 0 < a
            @[simp]
            theorem WithBot.coe_lt_one {α : Type u} [One α] {a : α} [LT α] :
            a < 1 a < 1
            @[simp]
            theorem WithBot.coe_lt_zero {α : Type u} [Zero α] {a : α} [LT α] :
            a < 0 a < 0
            @[simp]
            theorem WithBot.map_one {α : Type u} [One α] {β : Type u_1} (f : αβ) :
            map f 1 = (f 1)
            @[simp]
            theorem WithBot.map_zero {α : Type u} [Zero α] {β : Type u_1} (f : αβ) :
            map f 0 = (f 0)
            theorem WithBot.map_eq_one_iff {β : Type v} {α : Type u_1} {f : αβ} {v : WithBot α} [One β] :
            map f v = 1 (x : α), v = x f x = 1
            theorem WithBot.map_eq_zero_iff {β : Type v} {α : Type u_1} {f : αβ} {v : WithBot α} [Zero β] :
            map f v = 0 (x : α), v = x f x = 0
            theorem WithBot.one_eq_map_iff {β : Type v} {α : Type u_1} {f : αβ} {v : WithBot α} [One β] :
            1 = map f v (x : α), v = x f x = 1
            theorem WithBot.zero_eq_map_iff {β : Type v} {α : Type u_1} {f : αβ} {v : WithBot α} [Zero β] :
            0 = map f v (x : α), v = x f x = 0
            instance WithBot.zeroLEOneClass {α : Type u} [One α] [Zero α] [LE α] [ZeroLEOneClass α] :
            instance WithBot.add {α : Type u} [Add α] :
            Equations
            @[simp]
            theorem WithBot.coe_add {α : Type u} [Add α] (a b : α) :
            ↑(a + b) = a + b
            @[simp]
            theorem WithBot.bot_add {α : Type u} [Add α] (x : WithBot α) :
            @[simp]
            theorem WithBot.add_bot {α : Type u} [Add α] (x : WithBot α) :
            @[simp]
            theorem WithBot.add_eq_bot {α : Type u} [Add α] {x y : WithBot α} :
            x + y = x = y =
            theorem WithBot.add_ne_bot {α : Type u} [Add α] {x y : WithBot α} :
            @[simp]
            theorem WithBot.bot_lt_add {α : Type u} [Add α] {x y : WithBot α} [LT α] :
            < x + y < x < y
            theorem WithBot.add_eq_coe {α : Type u} [Add α] {a b : WithBot α} {c : α} :
            a + b = c (a' : α), (b' : α), a' = a b' = b a' + b' = c
            theorem WithBot.add_coe_eq_bot_iff {α : Type u} [Add α] {x : WithBot α} {b : α} :
            x + b = x =
            theorem WithBot.coe_add_eq_bot_iff {α : Type u} [Add α] {y : WithBot α} {a : α} :
            a + y = y =
            theorem WithBot.add_right_inj {α : Type u} [Add α] {x y z : WithBot α} [IsRightCancelAdd α] (hz : z ) :
            x + z = y + z x = y
            theorem WithBot.add_right_cancel {α : Type u} [Add α] {x y z : WithBot α} [IsRightCancelAdd α] (hz : z ) (h : x + z = y + z) :
            x = y
            theorem WithBot.add_left_inj {α : Type u} [Add α] {x y z : WithBot α} [IsLeftCancelAdd α] (hx : x ) :
            x + y = x + z y = z
            theorem WithBot.add_left_cancel {α : Type u} [Add α] {x y z : WithBot α} [IsLeftCancelAdd α] (hx : x ) (h : x + y = x + z) :
            y = z
            @[deprecated WithBot.add_left_inj (since := "2025-02-19")]
            theorem WithBot.add_left_cancel_iff {α : Type u} [Add α] {x y z : WithBot α} [IsLeftCancelAdd α] (hx : x ) :
            x + y = x + z y = z

            Alias of WithBot.add_left_inj.

            @[deprecated WithBot.add_right_inj (since := "2025-02-19")]
            theorem WithBot.add_right_cancel_iff {α : Type u} [Add α] {x y z : WithBot α} [IsRightCancelAdd α] (hz : z ) :
            x + z = y + z x = y

            Alias of WithBot.add_right_inj.

            instance WithBot.addLeftMono {α : Type u} [Add α] [LE α] [AddLeftMono α] :
            instance WithBot.addRightMono {α : Type u} [Add α] [LE α] [AddRightMono α] :
            theorem WithBot.le_of_add_le_add_left {α : Type u} [Add α] {x y z : WithBot α} [LE α] [AddLeftReflectLE α] (hx : x ) :
            x + y x + zy z
            theorem WithBot.le_of_add_le_add_right {α : Type u} [Add α] {x y z : WithBot α} [LE α] [AddRightReflectLE α] (hz : z ) :
            x + z y + zx y
            theorem WithBot.add_lt_add_left {α : Type u} [Add α] {x y z : WithBot α} [LT α] [AddLeftStrictMono α] (hx : x ) :
            y < zx + y < x + z
            theorem WithBot.add_lt_add_right {α : Type u} [Add α] {x y z : WithBot α} [LT α] [AddRightStrictMono α] (hz : z ) :
            x < yx + z < y + z
            theorem WithBot.add_le_add_iff_left {α : Type u} [Add α] {x y z : WithBot α} [LE α] [AddLeftMono α] [AddLeftReflectLE α] (hx : x ) :
            x + y x + z y z
            theorem WithBot.add_le_add_iff_right {α : Type u} [Add α] {x y z : WithBot α} [LE α] [AddRightMono α] [AddRightReflectLE α] (hz : z ) :
            x + z y + z x y
            theorem WithBot.add_lt_add_iff_left {α : Type u} [Add α] {x y z : WithBot α} [LT α] [AddLeftStrictMono α] [AddLeftReflectLT α] (hx : x ) :
            x + y < x + z y < z
            theorem WithBot.add_lt_add_iff_right {α : Type u} [Add α] {x y z : WithBot α} [LT α] [AddRightStrictMono α] [AddRightReflectLT α] (hz : z ) :
            x + z < y + z x < y
            theorem WithBot.add_lt_add_of_le_of_lt {α : Type u} [Add α] {w x y z : WithBot α} [Preorder α] [AddLeftStrictMono α] [AddRightMono α] (hw : w ) (hwy : w y) (hxz : x < z) :
            w + x < y + z
            theorem WithBot.add_lt_add_of_lt_of_le {α : Type u} [Add α] {w x y z : WithBot α} [Preorder α] [AddLeftMono α] [AddRightStrictMono α] (hx : x ) (hwy : w < y) (hxz : x z) :
            w + x < y + z
            theorem WithBot.addLECancellable_of_ne_bot {α : Type u} [Add α] {x : WithBot α} [Preorder α] [ContravariantClass α α (fun (x1 x2 : α) => x1 + x2) fun (x1 x2 : α) => x1 x2] (hx : x ) :
            theorem WithBot.addLECancellable_of_lt_bot {α : Type u} [Add α] {x : WithBot α} [Preorder α] [ContravariantClass α α (fun (x1 x2 : α) => x1 + x2) fun (x1 x2 : α) => x1 x2] (hx : x < ) :
            theorem WithBot.addLECancellable_coe {α : Type u} [Add α] [Preorder α] [ContravariantClass α α (fun (x1 x2 : α) => x1 + x2) fun (x1 x2 : α) => x1 x2] (a : α) :
            theorem WithBot.addLECancellable_iff_ne_bot {α : Type u} [Add α] {x : WithBot α} [Nonempty α] [Preorder α] [ContravariantClass α α (fun (x1 x2 : α) => x1 + x2) fun (x1 x2 : α) => x1 x2] :
            @[simp]
            theorem WithBot.map_add {α : Type u} {β : Type v} [Add α] {F : Type u_1} [Add β] [FunLike F α β] [AddHomClass F α β] (f : F) (a b : WithBot α) :
            map (⇑f) (a + b) = map (⇑f) a + map (⇑f) b
            def WithBot.addHom {α : Type u} [AddMonoid α] :

            Coercion from α to WithBot α as an AddMonoidHom.

            Equations
            Instances For
              @[simp]
              theorem WithBot.coe_addHom {α : Type u} [AddMonoid α] :
              @[simp]
              theorem WithBot.coe_nsmul {α : Type u} [AddMonoid α] (a : α) (n : ) :
              ↑(n a) = n a
              theorem WithBot.coe_natCast {α : Type u} [AddMonoidWithOne α] (n : ) :
              n = n
              @[simp]
              theorem WithBot.natCast_ne_bot {α : Type u} [AddMonoidWithOne α] (n : ) :
              n
              @[simp]
              theorem WithBot.bot_ne_natCast {α : Type u} [AddMonoidWithOne α] (n : ) :
              n
              @[simp]
              theorem WithBot.coe_ofNat {α : Type u} [AddMonoidWithOne α] (n : ) [n.AtLeastTwo] :
              @[simp]
              theorem WithBot.coe_eq_ofNat {α : Type u} [AddMonoidWithOne α] (n : ) [n.AtLeastTwo] (m : α) :
              @[simp]
              theorem WithBot.ofNat_eq_coe {α : Type u} [AddMonoidWithOne α] (n : ) [n.AtLeastTwo] (m : α) :
              @[simp]
              theorem WithBot.map_ofNat {α : Type u} {β : Type v} [AddMonoidWithOne α] {f : αβ} (n : ) [n.AtLeastTwo] :
              map f (OfNat.ofNat n) = (f (OfNat.ofNat n))
              @[simp]
              theorem WithBot.map_natCast {α : Type u} {β : Type v} [AddMonoidWithOne α] {f : αβ} (n : ) :
              map f n = (f n)
              theorem WithBot.map_eq_ofNat_iff {α : Type u} {β : Type v} [AddMonoidWithOne α] {f : βα} {n : } [n.AtLeastTwo] {a : WithBot β} :
              map f a = OfNat.ofNat n (x : β), a = x f x = n
              theorem WithBot.ofNat_eq_map_iff {α : Type u} {β : Type v} [AddMonoidWithOne α] {f : βα} {n : } [n.AtLeastTwo] {a : WithBot β} :
              OfNat.ofNat n = map f a (x : β), a = x f x = n
              theorem WithBot.map_eq_natCast_iff {α : Type u} {β : Type v} [AddMonoidWithOne α] {f : βα} {n : } {a : WithBot β} :
              map f a = n (x : β), a = x f x = n
              theorem WithBot.natCast_eq_map_iff {α : Type u} {β : Type v} [AddMonoidWithOne α] {f : βα} {n : } {a : WithBot β} :
              n = map f a (x : β), a = x f x = n
              def OneHom.withBotMap {M : Type u_1} {N : Type u_2} [One M] [One N] (f : OneHom M N) :

              A version of WithBot.map for OneHoms.

              Equations
              Instances For
                def ZeroHom.withBotMap {M : Type u_1} {N : Type u_2} [Zero M] [Zero N] (f : ZeroHom M N) :

                A version of WithBot.map for ZeroHoms

                Equations
                Instances For
                  @[simp]
                  theorem ZeroHom.withBotMap_apply {M : Type u_1} {N : Type u_2} [Zero M] [Zero N] (f : ZeroHom M N) :
                  @[simp]
                  theorem OneHom.withBotMap_apply {M : Type u_1} {N : Type u_2} [One M] [One N] (f : OneHom M N) :
                  def AddHom.withBotMap {M : Type u_1} {N : Type u_2} [Add M] [Add N] (f : M →ₙ+ N) :

                  A version of WithBot.map for AddHoms.

                  Equations
                  Instances For
                    @[simp]
                    theorem AddHom.withBotMap_apply {M : Type u_1} {N : Type u_2} [Add M] [Add N] (f : M →ₙ+ N) :
                    def AddMonoidHom.withBotMap {M : Type u_1} {N : Type u_2} [AddZeroClass M] [AddZeroClass N] (f : M →+ N) :

                    A version of WithBot.map for AddMonoidHoms.

                    Equations
                    Instances For
                      @[simp]
                      theorem AddMonoidHom.withBotMap_apply {M : Type u_1} {N : Type u_2} [AddZeroClass M] [AddZeroClass N] (f : M →+ N) :